2019
DOI: 10.1021/jacs.9b09227
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Stabilization of the [Pyridinium-CO2-Co] Adduct on a Metal–Organic Layer Enhances Electrocatalytic CO2 Reduction

Abstract: Pyridinium has been shown to be a cocatalyst for the electrochemical reduction of CO 2 on metal and semiconductor electrodes, but its exact role has been difficult to elucidate. In this work, we create cooperative cobaltprotoporphyrin (CoPP) and pyridine/pyridinium (py/pyH + ) catalytic sites on metal−organic layers (MOLs) for an electrocatalytic CO 2 reduction reaction (CO 2 RR). Constructed from [Hf 6 (μ 3 -O) 4 (μ 3 -OH) 4 (HCO 2 ) 6 ] secondary building units (SBUs) and terpyridine-based tricarboxylate lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 42 publications
2
101
0
Order By: Relevance
“…9). 168 Following a post-synthetic approach, CoPP moieties were incorporated into two different MOL backbone derivatives, built from benzenetribenzoate (BTB) and 4 0 -(4-benzoate)-(2,2 0 ,2 00 -terpyridine)-5,5 00dicarboxylate (TPY) linkers, respectively. In the TPY-MOL-CoPP material, the pyridine/pyridinium pendant groups adjacent to the CoPP active sites were found to engage a cooperative synergistic boosting effect on catalysis ( Fig.…”
Section: àmentioning
confidence: 99%
See 2 more Smart Citations
“…9). 168 Following a post-synthetic approach, CoPP moieties were incorporated into two different MOL backbone derivatives, built from benzenetribenzoate (BTB) and 4 0 -(4-benzoate)-(2,2 0 ,2 00 -terpyridine)-5,5 00dicarboxylate (TPY) linkers, respectively. In the TPY-MOL-CoPP material, the pyridine/pyridinium pendant groups adjacent to the CoPP active sites were found to engage a cooperative synergistic boosting effect on catalysis ( Fig.…”
Section: àmentioning
confidence: 99%
“…9c). 168 DFT calculations suggested that the pyridinium moieties of the framework exert a cooperative boosting effect by lowering the energy barrier for both, CO 2 adsorption and C-O bond cleavage, the latter being the ratedetermining step of the process. The proposed mechanism is analogous to the one above mentioned for the Co porphine system, 154 whereby the one-electron reduction of CoPP to [CoPP] À is followed by CO 2 binding and protonation steps, leading to the formation of the key [pyH-O 2 C-Co(PP)] 0 adduct, stabilized by a pre-positioned pyridine moiety to favor CO 2 RR over HER.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosizing MOFs into ultrathin metal-organic layers (MOLs) can e ciently accelerate mass transport / electron transfer and create abundant readily accessible active sites to ensure high activity in various catalytic reactions. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Moreover, ultrathin MOFs with limited number of atoms represent ideal models to explore structure-performance relationships for further rationally constructing e cient catalysts at atomic/molecular levels. For example, a mono-carboxylic bipyridine ligand was utilized to assemble Re-/Mn-Ru molecules into monolayer Hf-based MOLs, 20 the resulting Re-Ru-based MOLs can sustainably reduce CO 2 to CO under real sunlight for one week.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary coordination sphere effects, routinely employed by enzymes, 7 have been translated to both molecular 8,9 and heterogeneous [10][11][12][13] CO2R electrocatalysts. In the context of heterogeneous systems, CO2R performance has been successfully modulated through the use of grafted surface ligands which interact with adsorbed species or promote their transfer to the catalyst surface, [14][15][16][17][18][19] design of enzyme-mimetic catalytic pockets in porous materials, 20,21 and tuning of the electrolyte. [22][23][24] Complementary to CO2R system design is the innovation of operando techniques which provide mechanistic information on the reaction and are performed simultaneously as the reaction proceeds.…”
Section: Introductionmentioning
confidence: 99%